2021
DOI: 10.1136/medethics-2021-107498
|View full text |Cite
|
Sign up to set email alerts
|

Euthanasia and organ donation still firmly connected: reply to Bollen et al

Abstract: Bollen et al, replying to my own article, describe, in great detail, administrative and logistical aspects of euthanasia approval and organ donation in the Netherlands. They seem to believe that no useful lessons can be drawn from experiences of related groups such as euthanasia patients (typically patients with cancer) who cannot donate organs; patients who chose assisted suicide as opposed to euthanasia; patients in intensive care units and their relatives and suicidal young people as if we can only learn ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…There is an inevitable intertwining of care pathways and ongoing interactions with the OPO representatives/donor coordinator might influence the donor to maintain consent for MAiD and donation. The MAiD provider needs to understand the dynamics of human decision‐making and the inherent psychological processes of altruism and social desirability that could uniquely influence the MAiD consent process in the context of ODE (but not when MAiD is the only consideration) 146,150–154 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an inevitable intertwining of care pathways and ongoing interactions with the OPO representatives/donor coordinator might influence the donor to maintain consent for MAiD and donation. The MAiD provider needs to understand the dynamics of human decision‐making and the inherent psychological processes of altruism and social desirability that could uniquely influence the MAiD consent process in the context of ODE (but not when MAiD is the only consideration) 146,150–154 …”
Section: Discussionmentioning
confidence: 99%
“…The MAiD provider needs to understand the dynamics of human decision‐making and the inherent psychological processes of altruism and social desirability that could uniquely influence the MAiD consent process in the context of ODE (but not when MAiD is the only consideration). 146 , 150 , 151 , 152 , 153 , 154…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,8,12,27,32,77,95 Eligibility criteria for organ donation and MAiD Some authors 30,31 expressed a concern that enabling patients who request MAiD to donate their organs could lead to an expansion of the MAiD criteria to include individuals contemplating suicide as potential donors, since these individuals tend to be mostly young and physically healthy. Also, although suicidal individuals do not currently fulfill the requirements for MAiD, with the progress of practices and updates in legislation, Buturovic 30,31 stated a more extreme fear that the same authors who are currently defending organ donation following MAiD may soon be advocating for the inclusion of individuals with suicidal ideation to be eligible for MAiD to expand the donor pool. Another author 55 stated that patients who request MAiD should be treated differently than suicidal individuals, as the motivation to die may be generated by the desire for organ donation for patients who request MAiD.…”
Section: Ethics Dilemmas and Consensusmentioning
confidence: 99%
“…Some authors highlighted that, besides the need for informed consent at the beginning of the MAiD process, patients may also need to reconfirm consent right before the administration of the lethal drugs. 8,31,99 Also, if the patient's condition deteriorates in the days preceding the procedure, some authors suggested that new medical evaluations may be needed, 24 while others recommended that this conversation should be held beforehand with the patient. Also, some authors commented that, if acute deterioration happens at home, organ donation should not be performed 10 ; however, if deterioration happens in the hospital, then organ donation may proceed.…”
Section: Disclosure Of Donors' and Recipients' Informationmentioning
confidence: 99%